Numerical modeling of in-band pumped ho-doped silica fiber lasers - Wang, Jiachen; Yeom, Dong Il; Simakov, Nikita; Hemming, Alexander; Carter, Adrian; Lee, Sang Bae; Lee, Kwanil (Journal of Lightwave Technology, 2018)
A theoretical model to describe in-band pumped holmium doped silica fiber lasers is presented. The model is established based upon theory and parameters obtained from published research works. Both core-pumped system and cladding-pumped system are simulated with the model. The simulation results agree well with most experimental results, and for the cases in which the simulation results show discrepancy with the experimental results the disagreement can be reasonably explained. Through numerical analysis it is found that besides common negative factors such as non-radiative decay, fiber loss, and non-optimized resonator configuration, energy transfer upconversion plays a deleterious role in the performance of in-band pumped holmium doped silica fiber lasers. In particular, inhomogeneous upconversion associated with ion clustering is found to cause significant degradation of slope efficiencies of lasers, a fact that is useful to understand the unsolved problem regarding the lower-than-expected slope efficiencies observed in previous studies of in-band pumped holmium doped fiber lasers.
Keywords: Energy transfer upconversion; Nonradiative decays; Optical fiber theory; Pump laser; Resonator configuration; Slope efficiencies; Theoretical modeling; Unsolved problems; Holmium doped fiber lasers; laser theory; numerical analysis